Pengaruh Media Pembelajaran Menggunakan Wordwall untuk Meningkatkan Motivasi Belajar Siswa Kelas X pada Mata Pelajaran Bahasa Indonesia - Audina, Mia; Ahmad Fajri Lutfi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study is to determine whether there is a significant effect of the implementation of Wordwall as a learning medium to increase students' interest in learning, particularly students in grade X of the Indonesian Language subject at SMA Negeri 1 Kadugede. The method used in this research is a quantitative quasi-experimental type. The research design employs a Nonequivalent Control Group Pretest-Posttest Design. This study involved 394 students from classes XA and XB, each with 73 samples. Data collection techniques used included observation, questionnaires, and documentation. The research instrument is a questionnaire, which was used to administer pretests and posttests before and after the implementation of the learning media using Wordwall. Data analysis used a t-test. The results indicate a significant increase in learning motivation among grade X Indonesian language students, as evidenced by pretest and posttest scores: 62.51 and 70.02, respectively. These results suggest a significant increase in learning motivation among students after implementing Wordwall-based learning, with an increase of 7.51